Reinventing gut health: leveraging dietary bioactive compounds for the prevention and treatment of diseases - Wang, Qiurong; Huang, Hui; Yang, Ying; Yang, Xianglan; Li, Xuemei; Zhong, Wei; Wen, Biao; He, Feng; Li, Jun (Frontiers in Nutrition, 2024)
The human gut harbors a complex and diverse microbiota essential for maintaining health. Diet is the most significant modifiable factor influencing gut microbiota composition and function, particularly through bioactive compounds like polyphenols, dietary fibers, and carotenoids found in vegetables, fruits, seafood, coffee, and green tea. These compounds regulate the gut microbiota by promoting beneficial bacteria and suppressing harmful ones, leading to the production of key microbiota-derived metabolites such as short-chain fatty acids, bile acid derivatives, and tryptophan metabolites. These metabolites are crucial for gut homeostasis, influencing gut barrier function, immune responses, energy metabolism, anti-inflammatory processes, lipid digestion, and modulation of gut inflammation. This review outlines the regulatory impact of typical bioactive compounds on the gut microbiota and explores the connection between specific microbiota-derived metabolites and overall health. We discuss how dietary interventions can affect disease development and progression through mechanisms involving these metabolites. We examine the roles of bioactive compounds and their metabolites in the prevention and treatment of diseases including inflammatory bowel disease, colorectal cancer, cardiovascular diseases, obesity, and type 2 diabetes mellitus. This study provides new insights into disease prevention and underscores the potential of dietary modulation of the gut microbiota as a strategy for improving health.